Update on new therapeutic options for the somatopause - Ceda, Gian Paolo; Dall'Aglio, Elisabetta; Morganti, Simonetta; Denti, Licia; Maggio, Marcello; Lauretani, Fulvio; Artoni, Andrea; Ceresini, Graziano; Cattabiani, Chiara; Valenti, Giorgio (Acta Biomedica Atenei Parmensis, 2010)
During the last decade, a significant body of evidence has accumulated, indicating that the declining activity of the GH-IGF-I axis with aging might play a role in the development of frailty and in several pathological conditions commonly seen during aging, such as atherosclerosis, cardiovascular disease, and cognitive decline. GH therapy has become widely popular as antiaging therapy in order to counteract the age-related decline in muscle mass and strength and the increase in fat mass. However there are only few proven beneficial effects of GH therapy in healthy elderly subjects and its use remains highly controversial in the scientific community. In this paper we will review the current evidence related to the use of GH and/or GH-secretagogues in normal and pathological aging.